PENGARUH TERAPI MUSIK TERHADAP PENURUNAN NYERI PERSALINAN: EVIDENCE BASED CASE REPORT (Politeknik Kesehatan Kemenkes Bandung, 2023)
Strong contractions in the uterus that cause pain are a sign of labor. Pain feelings are subjective and arise because of a sense of discomfort in a person. Solutions to reduce pain in laboring mothers will be beneficial for the mother and the fetus. Music therapy is an effective solution for mothers who experience pain during labor because music affects pain by distracting, relaxing, and creating a sense of comfort. The purpose of this study is to apply music therapy to reduce pain in women in the 1st stage of labor. The method used is to search evidence through PubMed and Cochrane databases published in 2018-2023. Results: The case report shows that music therapy can reduce labor pain in women who give birth with pain. Music therapy reduces labor pain in giving birth to mothers.